Revisiting hydrophobicity and its effectiveness in oil retention using microfluidic experiments - Kyung-Jin Lee; Ah Hyeon Lee; Seunghak Lee; Sang Hyun Kim; Jaeshik Chung (npj Clean Water)
Abstract We examined oil-water displacement under constant pressure difference conditions, simulating natural aquifer environments using microfluidic chips with different wettability and pore geometries. The results showed lower oil retention in hydrophobic chips than hydrophilic ones, contrary to previous microfluidic chip experiments conducted under constant flow rate conditions. This is because hydrophobic surfaces reduce capillary pressure drop but increase viscous pressure drop for compensation, leading to higher flow rate and displacement. Additionally, complex pore geometries in hydrophilic chips cause oil clusters to break into smaller blobs, reducing retention and enhancing the relative permeability of water. These findings suggest that relying solely on hydrophobicity may be ineffective in retaining oil in porous materials under constant pressure difference conditions, highlighting the need for more careful consideration in groundwater remediation design.